IDENTIFICATION AND CROSS INOCULATION OF Colletotrichum gloeosporioides ASSOCIATED IN MANDARIN CITRUS - Ulilalbab, Azizah Ridha; Miftahul Ajri; Wicaksono, Danar; Poerwanto, Mofit Eko; Kuncoro, Seto Agung; Dhamira, Aura (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2025)
Colletotrichum spp are important post-harvest pathogens that frequently cause anthracnose and significant quality deterioration in citrus. This study were aimed to identify morphological characteristics and genetic confirmation of Colletotrichum isolates associated with mandarin citrus , as well as to evaluate the cross-inoculation potential of these isolates among five post-harvest commodities. Anthracnose-infected citrus fruits were collected from a local market in Central Java, Indonesia. Fungal isolation was conducted using the single-spore technique, and identification was based on colony and conidial characteristics, followed by PCR amplification with the universal ITS1 and ITS4 primers. Cross-inoculation tests were performed on five post-harvest commodities. Morphological and genetic characteristics indicated that the isolates referred to Colletotrichum gloeosporioides, the causal agent of anthracnose in mandarin citrus. Colony characters were white-greyish colour with velvety texture, conidiomata, black spots, concentric rings, and fast-growing group. Conidia were cylindrical with rounded ends, measuring 12.02µm in length and 4.23µm in width on average. ITS amplification yielded a ±570 bp fragment that showed 98% similarity to C. gloeosporioides isolates from China, indicating a close relationship with the C. gloeosporioides species complex. Cross-inoculation tests showed that C. gloeosporioides can cause anthracnose symptoms in tomato, cayenne, pepper, citrus, and mango. The finding highlights that C. gloeosporioides was detected on mandarin fruits exhibiting anthracnose symptoms, and the potency of the cross-inoculation assay revealed the broad host range of this fungus.